Cultivating Religious Moderation Based on KOMPAQ at Universitas Muhammadiyah Bengkulu - Dhimas Alunandika; Faridi; Moh Nurhakim (Didaktika: Jurnal Kependidikan, 2024)
They are cultivating moderation at Universitas Muhammadiyah Bengkulu, based in Kompaq. Religious moderation is significant in creating harmony amidst diversity in multicultural Indonesia. This research aims to study how university students understand and apply religious moderation and how it impacts their attitudes towards tolerance and interfaith harmony. This research was conducted qualitatively with a Postpositivism approach involving participatory observation and in-depth interviews. The results showed that students of Universitas Muhammadiyah Bengkulu understand religious moderation well, which is reflected in their mutual respect and tolerance for differences. In addition, it has been proven that applying religious moderation values helps reduce the likelihood of conflict and increase cooperation between religious groups. The cultivation of Kompaq-based religious moderation at this university affects the entire campus community. The academic environment is expected to be inclusive and harmonious with social activities and educational programs that support moderate values. This study dramatically helps us understand the dynamics of religious moderation among the younger generation and offers suggestions for building religious moderation programs in other educational institutions.